The day my butt went psycho! - Griffiths, Andy, 1961- (New York : Scholastic, 2003)
Zack Freeman joins forces with the B-Team squad in an effort to stop a plot by the world's butts--including Zack's own backside--to take what they believe to be their rightful place on the human body.
4.7
3-6
Keywords: Buttocks -- Juvenile fiction; Heroes -- Juvenile fiction; Buttocks -- Fiction; Heroes -- Fiction; Humorous stories; Science fiction; Buttocks -- Fiction; Heroes and heroines -- Fiction; Humorous fiction; Science fiction; Humorous fiction; Science fiction